The role of heat shock proteins in preventing amyloid toxicity - Törner, Ricarda; Kupreichyk, Tatsiana; Hoyer, Wolfgang; Boisbouvier, Jerome (Frontiers in Molecular Biosciences, 2022)
The oligomerization of monomeric proteins into large, elongated, β-sheet-rich fibril structures (amyloid), which results in toxicity to impacted cells, is highly correlated to increased age. The concomitant decrease of the quality control system, composed of chaperones, ubiquitin-proteasome system and autophagy-lysosomal pathway, has been shown to play an important role in disease development. In the last years an increasing number of studies has been published which focus on chaperones, modulators of protein conformational states, and their effects on preventing amyloid toxicity. Here, we give a comprehensive overview of the current understanding of chaperones and amyloidogenic proteins and summarize the advances made in elucidating the impact of these two classes of proteins on each other, whilst also highlighting challenges and remaining open questions. The focus of this review is on structural and mechanistic studies and its aim is to bring novices of this field “up to speed” by providing insight into all the relevant processes and presenting seminal structural and functional investigations.